2009
DOI: 10.1103/physreva.79.033847
|View full text |Cite
|
Sign up to set email alerts
|

Discrete diffraction and shape-invariant beams in optical waveguide arrays

Abstract: General properties of linear propagation of discretized light in homogeneous and curved waveguide arrays are comprehensively investigated and compared to those of paraxial diffraction in continuous media. In particular, general laws describing beam spreading, beam decay and discrete far-field patterns in homogeneous arrays are derived using the method of moments and the steepest descend method. In curved arrays, the method of moments is extended to describe evolution of global beam parameters. A family of beam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 59 publications
(78 reference statements)
0
30
0
Order By: Relevance
“…For coupled waveguides without damping, special attention has been given to the time evolution of the NOON states as inputs and we have shown that as we increase the photon number, the entanglement of the NOON states survives with time, thus making them extremely suitable for quantum information. The solution for damped systems was obtained by transforming the master equation to a Schrodinger type equation and applying the disentanglement formulae for SU (2) and SU(1, 1). Our work extends that of Rai et al [4], as it gives the exact solution for the master equation, and, in addition shows how the entanglement behaves for input thermal states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For coupled waveguides without damping, special attention has been given to the time evolution of the NOON states as inputs and we have shown that as we increase the photon number, the entanglement of the NOON states survives with time, thus making them extremely suitable for quantum information. The solution for damped systems was obtained by transforming the master equation to a Schrodinger type equation and applying the disentanglement formulae for SU (2) and SU(1, 1). Our work extends that of Rai et al [4], as it gives the exact solution for the master equation, and, in addition shows how the entanglement behaves for input thermal states.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the problem of solving master equation is reduced to solving a Schrodinger like equation. Symmetries associated with the Hamiltonian (such as SU (2) and SU(1, 1) symmetries) can be exploited to solve the master equation. This makes the study of entanglement in lossy systems very tractable.…”
Section: Thermofield Dynamicsmentioning
confidence: 99%
“…In addition to the defect modes, the input beams also excite Bloch-Floquet modes of the periodic array, which are dispersive waves, i.e., they diffract as the propagation distance z increases and tend to delocalize light over the various waveguides of the lattice [25]. Therefore, after an initial transient, the light that remains trapped near the defect region arises from the initially excited localized modes.…”
Section: Classical Description Of Light Trapping In a Photonic Lamentioning
confidence: 99%
“…At present, the physics of one-and two-dimensional infinite fibre arrays has been studied in detail in a number of works [2][3][4]. This is partially explained by a novel phenomenon of discrete diffraction, which takes place in waveguide arrays [5,6]. Some interesting results have been obtained for the curved [7] and nonlinear [8,9] waveguide arrays.…”
Section: Introductionmentioning
confidence: 99%